Vetera et nova in materia di offese a una confessione religiosa mediante vilipendio di persone (art. 403 c.p.) e di turbatio sacrorum (art. 405 c.p.) - Benato, Edoardo (Il diritto ecclesiastico, 2024)
Old things and new ones about the offence against a religious confession by vilification of persons (art. 403 of the Criminal Vode) and turbatio sacrorum (art. 405 of the Criminal Code) · In the postmodern era, there are new ways of conceiving the religious phenomenon, which are able to affect the conception of the juridical asset protected by Chapter i of Title iv of Book ii of the Penal Code. The legal paradigms of reference, although they need to be updated, have not been subjected to normative interventions for almost twenty years now. In particular, the definition of vilification, relevant pursuant to par. 403 of the Criminal Code, is still affected by a certain vagueness. In addition, the new perception of the protected asset affects the qualification of the disturbance of the religious manifestations, relevant pursuant to par. 405 of the Criminal Code, making its nature increasingly volatile. In the face of the persistent inertia of the Legislator, the Supreme Court has shown a renewed interest for the subject, with two recent sentences that have delimited the boundary between vilification and religious criticism and significantly expanded the application scope of the turbatio sacrorum.